PROFESSIONAL EXAMINATIONS. - Chamberlain, Henry T. (The Accounting Review, 1940)
The article focuses on various problems, which were prepared by the Board of Examiners of the American Institute of Certified Public Accountants (CPA) and were presented as the second half of the May 1940 CPA examination in accounting practice. The examinee was given six hours to solve problems 1, 2, 3 and either problem 4 or 5. Problems were weighted as follows: problem 1, 10 points; problem 2, 25 points; problem 3, 30 points; problems 4 and 5, 33 points each. In one question, details of two hypothetical companies namely A and B, which are entirely owned and controlled by same interests, are presented. The company A's condensed balanced-sheet for a particular year is presented in the article. In another question, another hypothetical company, namely, S.S. Manufacturing Co. is discussed, which completed construction of its plant for the manufacture of lawn mowers on January 1, 1939 and commenced manufacturing on January 13, 1939. The examinee is required to restate the actual and standard production costs for the thirty-day operating period and show the estimated loss by theft of the 500 lawn mowers.